2006
DOI: 10.1086/507427
|View full text |Cite
|
Sign up to set email alerts
|

Region of Difference 1 Antigen–Specific CD4+Memory T Cells Correlate with a Favorable Outcome of Tuberculosis

Abstract: These data suggest a protective role for RD1 peptide-specific CD4+ effector T cells, which undergo clonal expansion during Mycobacterium tuberculosis replication and then a contraction phase after disease resolution, culminating in the generation of CD4+ memory T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
96
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 30 publications
12
96
1
Order By: Relevance
“…It has been shown by flow cytometry that the T-cells responding to the RD antigens after 24-h stimulation are predominantly CD4 T-cells of an effector memory phenotype, characterised as being CD45RA-CCR7-, consistent with having recently encountered antigen in vivo [11,12,36,37]. In contrast, long-lived central memory T-cells that may persist even after successful treatment of tuberculosis [11,12,36,37,56,57] are less likely to release IFN-c after ,24 h of incubation and more likely to produce IL-2 [56].…”
Section: Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown by flow cytometry that the T-cells responding to the RD antigens after 24-h stimulation are predominantly CD4 T-cells of an effector memory phenotype, characterised as being CD45RA-CCR7-, consistent with having recently encountered antigen in vivo [11,12,36,37]. In contrast, long-lived central memory T-cells that may persist even after successful treatment of tuberculosis [11,12,36,37,56,57] are less likely to release IFN-c after ,24 h of incubation and more likely to produce IL-2 [56].…”
Section: Sectionmentioning
confidence: 99%
“…In contrast, long-lived central memory T-cells that may persist even after successful treatment of tuberculosis [11,12,36,37,56,57] are less likely to release IFN-c after ,24 h of incubation and more likely to produce IL-2 [56].…”
Section: Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…New diagnostic approaches are needed that allow for a more targeted identification of patients at risk to develop TB. This may involve modifications of in vitro immunodiagnostic assays such as the use of novel stimulatory antigens [15,164,165], alternative biomarkers other than IFN-c [166][167][168][169][170][171][172], variations in incubation time [173,174], the readout system [9,12,13,175,176] or the clinical specimen instead of blood [177][178][179]. In addition, both for the detection of LTBI with a risk of reactivation and for suspected active TB, a novel approach based on a whole blood transcriptional signature could provide a biomarker system with high discriminative potential [180].…”
Section: Improvements In the Diagnosis Of Ltbi In Transplant Candidatmentioning
confidence: 99%
“…The reactivity of effector T cells would then decrease as a result of antigen withdrawal as the level of production of IFN-␥ from a single immune cell decreased after treatment. It has been shown that IFN-␥ production after 24 h of stimulation fades upon treatment and correlates with the development of memory T cells (10). Cytokine production might also change after treatment, as recently suggested (24).…”
Section: Discussionmentioning
confidence: 90%